High-toughness polyurethane and preparation method thereof

By designing a microphase separation structure and introducing imidazolidinyl urea, the balance between strength and flexibility in polyurethane materials was solved, resulting in polyurethane materials with high mechanical strength and excellent toughness.

CN121293462APending Publication Date: 2026-01-09ANHUI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511715362.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-21
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Existing polyurethane materials struggle to strike a balance between improving strength and flexibility, making them prone to deformation and damage during use.

Method used

By employing a microphase separation structure design, PCL is prepolymerized with PPGTD and IPDI via a prepolymerization method, and then imidazolidinyl urea is added to form a copolymerization reaction, resulting in a polyurethane material with dynamic properties and flexibility.

Benefits of technology

It improves the mechanical strength and crack propagation resistance of polyurethane materials, enhances their fatigue resistance and durability, and exhibits excellent toughness and energy absorption capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121293462A_ABST
    Figure CN121293462A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polyurethane materials, and particularly discloses high-toughness polyurethane and a preparation method thereof.The high-toughness polyurethane is prepared from, by mass, 8.3% of imidazolidinyl urea, 44.6% of polycaprolactone, 41% of polypropylene glycol and 1% of isophorone diisocyanate, the mass percentage of the polycaprolactone is 44.6%, the mass percentage of the polypropylene glycol is 44.6%, and the mass percentage of the isophorone diisocyanate is 44.6%. The mass percent of the isophorone diisocyanate is 5.9%. Through the design of a microphase separation structure, the high-toughness polyurethane material is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyurethane materials technology, and in particular to a high-toughness polyurethane and its preparation method. Background Technology

[0002] The strength of polyurethane directly determines its ability to resist external forces and prevent deformation and damage during use. The flexibility of polyurethane also plays a crucial role in its fatigue resistance and crack propagation resistance, thus affecting the product's durability. How to simultaneously improve the strength and flexibility of polyurethane is a long-term problem that needs to be solved.

[0003] Isophorone diisocyanate (IPDI) is widely used in the preparation of room-temperature self-healing polyurethanes or polyurea elastomers. The asymmetric alicyclic structure of IPDI leads to the formation of loosely packed hard domains, enhancing the local mobility of the molecular chains and promoting the dynamic exchange of hydrogen bonds. However, amorphous hard domains typically do not provide sufficient mechanical strength. Summary of the Invention

[0004] The purpose of this invention is to address the shortcomings of existing technologies by proposing a method for preparing high-toughness polyurethane.

[0005] To achieve the above objectives, the present invention adopts the following technical solution: A high-toughness polyurethane material includes imidazolidinyl urea; the imidazolidinyl urea accounts for 8.3% by mass percentage.

[0006] Preferably, it also includes polycaprolactone, polypropylene glycol, and isophorone diisocyanate.

[0007] Preferably, the polycaprolactone has a mass percentage of 44.6%, the polypropylene glycol has a mass percentage of 41%, and the isophorone diisocyanate has a mass percentage of 5.9%.

[0008] A method for preparing a high-toughness polyurethane material, the method comprising the following steps: Step 1: First, put polycaprolactone into a flask and heat it in a hot oil pan to remove the water vapor it contains; Step 2: Dissolve polypropylene glycol (PPGTD, toluene-2,4-diisocyanate-terminated) and isophorone diisocyanate in N,N-dimethylformamide (DMF) and stir until the solution is clear to obtain solution A. Add solution A to the above flask and then add dibutyltin dilaurate (DBTDL) dropwise to carry out the prepolymerization reaction. Step 3: After prepolymerization, dissolve imidazolidinyl urea in N,N-dimethylformamide (DMF) and add it to the flask mentioned above; Step 4: Finally, pour it into the mold, dry it on a constant temperature heating table, and then transfer it to an oven to dry.

[0009] Preferably, in step one, polycaprolactone is placed in a flask and heated in an oil pan at 120°C for 20 minutes.

[0010] Preferably, the polypropylene glycol in step two is toluene-2,4-diisocyanate-terminated polypropylene glycol.

[0011] Preferably, in step three, imidazolidinyl urea is dissolved in N,N-dimethylformamide (DMF) and added to the above-mentioned flask for reaction for three hours.

[0012] Preferably, in step four, the product is dried on a 90°C constant temperature heating table for 12 hours and then dried in an 80°C oven for 24 hours.

[0013] Preferably, the prepolymerization reaction in step two lasts for 1 hour.

[0014] The application of a high-toughness polyurethane material in PU production as described above.

[0015] Compared with the prior art, the beneficial effects of the present invention are: This invention employs a microphase separation structure design strategy. First, PCL is prepolymerized with PPGTD and IPDI using a prepolymer method. Under the catalysis of DBTDL, PCL-PPGTD and PCL-IPDI prepolymers are generated. PPGTD provides flexibility and elasticity, forming soft segments. The asymmetric structure of IPDI leads to the formation of amorphous hard domains, which helps maintain the dynamic properties and flexibility of polyurethane while providing good mechanical strength. PCL segments have high crystallinity and strength, enhancing the mechanical properties of the polyurethane elastomer. Then, IU, containing a rigid structure, is added to the prepolymer to gradually complete the copolymerization reaction, forming the final polyurethane elastomer. IU further enhances the mechanical properties of PU through its abundant hydrogen bond donor and acceptor properties. Attached Figure Description

[0016] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0017] Figure 1 Fourier transform infrared (FTIR) spectra of the dynamically crosslinked polyurethane elastomers prepared in Example 1, Comparative Example 1, and Comparative Example 2. Figure 2The temperature dependence of the storage modulus (E′) of the dynamically crosslinked polyurethane elastomers prepared in Example 1, Comparative Example 1, and Comparative Example 2 is shown. Figure 3 Temperature dependence curves of the damping factor (tan δ) of the dynamically crosslinked polyurethane elastomers prepared in Example 1, Comparative Example 1, and Comparative Example 2. Figure 4 The stress-strain curves of the dynamically crosslinked polyurethane elastomers prepared in Example 1, Comparative Example 1, and Comparative Example 2 are shown. Figure 5 The tensile strength histograms of the dynamically cross-linked polyurethane elastomers prepared in Example 1, Comparative Example 1, and Comparative Example 2 are shown. Figure 6 The bar chart shows the elongation at break of the dynamically cross-linked polyurethane elastomers prepared in Example 1, Comparative Example 1, and Comparative Example 2.

[0018] Figure 7 This is a puncture test diagram of the dynamically cross-linked polyurethane elastomer prepared in Example 1.

[0019] Figure 8 Example 1 shows the puncture force versus displacement curve of the dynamically cross-linked polyurethane elastomer. Detailed Implementation

[0020] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0021] Poly(ε-caprolactone) (PCL, number average molecular weight Mn = 2000 g / mol) (Aladdin), Poly(propylene glycol, toluene-2,4-diisocyanate-terminated) (PPGTD, isocyanate content approximately 3.6 wt%, Casamart), Isophorone diisocyanate (IPDI) (Aladdin), imidazolidinyl urea (IU) (Aladdin), and dibutyltin dilaurate (DBTDL) (Aladdin).

[0022] Example 1 Weigh 7.5g of polycaprolactone into a flask and heat it in an oil bath at 120°C for 20 minutes to remove any water vapor. Then, adjust the oil bath temperature to 75°C. Dissolve 6.9g of PPGTD and 1g of IPDI in 12.5ml of N,N-dimethylformamide (DMF) and stir until the solution is clear. Then, add this solution dropwise to the flask above, followed by 5 drops of DBTDL for prepolymerization for 1 hour. After prepolymerization, dissolve 1.4g of IU in 62.5ml of N,N-dimethylformamide (DMF) and add it to the flask above, reacting for three hours. Finally, pour the solution into a mold and dry it on a 90°C constant temperature heating table for 12 hours, then transfer it to an 80°C oven and dry it for 24 hours. This yields a transparent polycaprolactone-based polyurethane material (PIPU).

[0023] Comparative Example 1 Weigh 12g of polycaprolactone and place it in a flask. Then heat it in an oil bath at 120°C for 20 minutes to remove any water vapor. Next, adjust the oil bath temperature to 75°C. Dissolve 5.5g of PPGTD and 0.8g of IPDI in 50ml of N,N-dimethylformamide (DMF) and stir until the solution is clear. Then add this solution dropwise to the flask above, followed by 5 drops of DBTDL for prepolymerization for 1 hour. After prepolymerization is complete, add the solution back to the flask and react for three hours. Finally, pour the solution into a mold and dry it on a 90°C constant temperature heating table for 12 hours. Then transfer it to an 80°C oven and dry it for 24 hours to obtain polyurethane material (PCLU).

[0024] Comparative Example 2 First, heat the oil pan to 75°C. Dissolve 11.0g PPGTD and 1.6g IPDI in 20ml N,N-dimethylformamide (DMF) and stir until the solution is clear. Then, add this solution dropwise to the above flask, followed by 5 drops of DBTDL for prepolymerization for 1 hour. After prepolymerization, dissolve 4.6g IU in 180ml N,N-dimethylformamide (DMF) and add this solution to the above flask to react for three hours. Finally, pour the solution into a mold and dry it on a 90°C constant temperature heating table for 12 hours. Then, transfer it to an 80°C oven and dry it for 24 hours to obtain the polyurethane material (IUPU).

[0025] Analysis and Conclusion The dynamically crosslinked polyurethane elastomers (PUs) prepared in Example 1, Comparative Example 1, and Comparative Example 2 were subjected to Fourier transform infrared spectroscopy (FTIR) testing. The test results are as follows: Figure 1 As shown. At 3328cm -1 and 1542cm -1 The characteristic peaks appearing at 1705 cm⁻¹ are the stretching vibration peak of NH in the urethane (-NH-COO-) group and the bending vibration peak of C=O, respectively. -1The peak appearing at 1109 cm⁻¹ is attributed to the CO bond in the urethane (-NH-COO-) group. -1 The broad vibrational peak at 2240-2280 cm⁻¹ is mainly due to the stretching vibration of COC in the polyether molecular chain. In the PU system, this peak occurs at 2240-2280 cm⁻¹. -1 No vibrational peak was observed at 1730 cm⁻¹. This confirms the complete reaction of the -NCO group, indicating that all IPDI monomers reacted completely and successfully to prepare PIPU. Compared to PCLU-type polyurethanes, PIPU exhibits a higher vibrational peak at 1730 cm⁻¹. -1 The intensity of the absorption peak (carbonyl group, C=O in polyurethane) decreased accordingly, indicating that the introduction of IU changed the ratio of polyurethane and urea groups in the hard domain, and altered the chemical structure and hydrogen bond network of the hard domain of PCLU-type polyurethane.

[0026] Figure 2 This represents the temperature dependence of the storage modulus (E′) of the three polyurethane elastomers. At low temperatures, the storage modulus of the three polyurethanes is ranked as IUPU > PIPU > PCLU. A higher storage modulus at low temperatures indicates higher rigidity.

[0027] Figure 3 This is the temperature dependence curve of the damping factor (tan δ) obtained through DMA. The effective damping temperature range is (tan δmin) > 0.3. It can be seen that the tan δmax of PIPU is much higher than that of PCLU and IUPU, indicating that the energy dissipation capacity of PIPU material under dynamic load is improved. The higher damping factor of PIPU is due to the good microphase separation between the hard and soft segments. PCLU-type polyurethane exhibits two damping peaks, indicating that it does not exhibit good microphase separation; the two damping peaks correspond to the glass transitions of the hard and soft segments, respectively.

[0028] Figure 4 The stress-strain curves of the dynamically cross-linked polyurethane elastomers prepared in Example 1, Comparative Example 1, and Comparative Example 2 are shown in yellow. The yellow curves show a trend of continuous and stable increase in stress with strain, and the curves are very long, indicating a very large strain at fracture. This reflects that PIPU material has excellent toughness and ductility, and the molecular chains have good flexibility and mobility, enabling it to deform to a large extent without breaking.

[0029] Figure 5 The bar charts for the tensile strength of dynamically crosslinked polyurethane elastomers prepared in Example 1, Comparative Example 1, and Comparative Example 2 show that PIPU has the highest tensile strength value, significantly higher than PCLU and IUPU. This means that PIPU material can withstand greater external forces before fracturing under tensile stress.

[0030] Figure 6The bar charts for the elongation at break of dynamically crosslinked polyurethane elastomers prepared in Example 1, Comparative Example 1, and Comparative Example 2 show that the elongation at break of PIPU far exceeds that of PCLU and IUPU, reaching a very high value. This fully demonstrates that PIPU material possesses excellent toughness.

[0031] Figure 7 , Figure 8 The images and data show the puncture test results of the dynamically cross-linked polyurethane elastomer prepared in Example 1. The properties of the polyurethane (PIPU) material provided by this invention were characterized using a standard puncture testing apparatus. This apparatus includes a puncture needle, an adjustable support column, and a sample fixing platform, ensuring that a 1 mm diameter puncture needle can be perpendicularly applied to the surface of a 0.8 mm thick PIPU sample. The test results are as follows... Figure 8 As shown in the force-displacement curve, this curve fully records the material's mechanical response from initial deformation to final puncture: as the needle displacement increases to approximately 18 mm, the puncture force continuously rises to a peak of approximately 16.08 N, indicating that the material underwent significant elastic and plastic deformation at this stage, absorbing a large amount of energy; subsequently, when the displacement continues to increase to approximately 20 mm, the puncture force drops sharply, indicating that the material has been completely punctured. The high peak puncture force and smooth force-displacement curve exhibited by this polyurethane material in the puncture test demonstrate its excellent puncture resistance and energy absorption capacity. Based on this characteristic, this polyurethane material has broad application prospects in safety protection equipment, special packaging materials, flexible composite materials, and other fields requiring high mechanical strength and durability.

[0032] Imidazolidinyl urea (IU) molecules contain abundant hydrogen bond donors and acceptors, enabling them to form multiple hydrogen bonds with polypropylene glycol (PPGTD) and polycaprolactone (PCL) segments. These hydrogen bonds act as physical crosslinking points, enhancing the internal structural stability of polyurethane. Imidazolidinyl urea prevents excessive aggregation of the PU network through hydrogen bonding, thereby avoiding the degradation of mechanical properties caused by uneven phase separation.

[0033] The present invention firstly synthesizes a polyurethane elastomer with excellent dynamic crosslinking, which significantly improves mechanical properties compared to ordinary polyurethane materials, providing a better option for subsequent polyurethane modification.

[0034] The embodiments described above fully demonstrate the feasibility of the technical concept and means proposed in this invention. Their purpose is to illustrate the implementation steps of this invention in detail, but they are not intended to limit the scope of protection of this invention. Based on the principles disclosed in this invention, those skilled in the art can make various modifications and improvements without departing from the essence and scope of this invention. Therefore, all equivalent transformations and improvements made based on the principles of this invention should be included within the scope of protection of this invention.

[0035] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A material based on high-toughness polyurethane, characterized in that, Includes imidazolidinyl urea; by weight, imidazolidinyl urea accounts for 8.3%.

2. The high-toughness polyurethane material according to claim 1, characterized in that, It also includes polycaprolactone, polypropylene glycol, and isophorone diisocyanate.

3. The high-toughness polyurethane material according to claim 2, characterized in that, The polycaprolactone comprises 44.6% by mass, the polypropylene glycol comprises 41% by mass, and the isophorone diisocyanate comprises 5.9% by mass.

4. A method for preparing a high-toughness polyurethane material, characterized in that, The preparation method of the high-toughness polyurethane includes the following steps: Step 1: First, put polycaprolactone into a flask and heat it in a hot oil pan to remove the water vapor it contains; Step 2: Dissolve polypropylene glycol and isophorone diisocyanate in N,N-dimethylformamide and stir until the solution is clear to obtain solution A. Add solution A to the above flask and then add dibutyltin dilaurate dropwise to carry out the prepolymerization reaction. Step 3: After the prepolymerization reaction is completed, dissolve imidazolidinyl urea in N,N-dimethylformamide and add it to the above flask for reaction; Step 4: Finally, pour it into the mold, dry it on a constant temperature heating table, and then transfer it to an oven to dry.

5. The method for preparing a high-toughness polyurethane according to claim 4, characterized in that, In step one, polycaprolactone is placed in a flask and heated in an oil pan at 120°C for 20 minutes.

6. The method for preparing a high-toughness polyurethane material according to claim 4, characterized in that, The polypropylene glycol in step two is toluene-2,4-diisocyanate-terminated polypropylene glycol.

7. The method for preparing a high-toughness polyurethane material according to claim 4, characterized in that, In step three, imidazolidinyl urea is dissolved in N,N-dimethylformamide and added to a flask to react for three hours.

8. The method for preparing a high-toughness polyurethane material according to claim 4, characterized in that, Step 4: Dry on a 90°C constant temperature heating table for 12 hours, and then dry in an 80°C oven for 24 hours.

9. The method for preparing a high-toughness polyurethane material according to claim 4, characterized in that, The prepolymerization reaction in step two lasts for 1 hour.

10. The application of a high-toughness polyurethane material according to any one of claims 1-3 in PU production.